2006
DOI: 10.1016/j.dld.2006.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Acid-suppressive effects of generic omeprazole: Comparison of three brands of generic omeprazole with original omeprazole

Abstract: Acid-suppressive effects of some brands of generic omeprazole are not the same as original omeprazole. These differences might be reflected in clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Esomeprazole 20 mg daily has proven effective for maintenance therapy of erosive GERD, 14,15 for on-demand therapy in non-erosive GERD 25,26 and for prevention of gastroduodenal ulcers in patients with nonsteroidal anti-inflammatory drugs. 27 As other intragastric pH studies and pharmaceutical studies have suggested significant differences between different generic omeprazole products, 17,18 the question remains whether generic omeprazole can provide a similar clinical efficacy as other original PPI brands. Although the results of our intragastric pH study can not be directly transferred to clinical outcomes, we speculate that the generic omeprazole used in our study with a daily dose of 20 mg might offer a similar clinical benefit in the treatment of acid-related gastroduodenal disorders as other original brand PPIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esomeprazole 20 mg daily has proven effective for maintenance therapy of erosive GERD, 14,15 for on-demand therapy in non-erosive GERD 25,26 and for prevention of gastroduodenal ulcers in patients with nonsteroidal anti-inflammatory drugs. 27 As other intragastric pH studies and pharmaceutical studies have suggested significant differences between different generic omeprazole products, 17,18 the question remains whether generic omeprazole can provide a similar clinical efficacy as other original PPI brands. Although the results of our intragastric pH study can not be directly transferred to clinical outcomes, we speculate that the generic omeprazole used in our study with a daily dose of 20 mg might offer a similar clinical benefit in the treatment of acid-related gastroduodenal disorders as other original brand PPIs.…”
Section: Discussionmentioning
confidence: 99%
“…A randomised study in Japanese healthy subjects demonstrated significant differences in intragastric acid control between one original and two generic omeprazole brands. 17 Finally, a comparative study of 25 non-Astra authorised omeprazole products suggests significant pharmaceutical differences between various products after storage under forced conditions. 18 Due to differences in the enzymatic hepatic metabolism, the racemic omeprazole and the s-isomer esomeprazole differ in their pharmacokinetic and pharmacodynamic profile.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is also large variability in the onset of action between different PPIs and between brand and generic formulas (inter-PPI variability) [16, 17, 28, 29]. Due to these factors, in theory, the delayed onset of action may be significantly shorter.…”
Section: Unraveling Drug–drug Interactions Between Tyrosine Kinase Inmentioning
confidence: 99%
“…Moreover, some authors35 argued that switching from brand antiepileptics to generic copies might result in an increased risk of therapeutic failure (breakthrough seizures) or adverse reactions. Other examples of treatment failure, with marketed antibiotic,6 anticoagulant,7 proton-pump inhibitor,8,9 antiarrhythmic,10 or antidepressant11 generic products, have also been published. Thus, the validity of current criteria for assessing interchangeability of generic and branded drugs is being questioned, at least in some instances, and it is becoming evident that inadequate programs for postmarketing quality control of medicinal products might increase the risk of therapeutic failures and/or safety concerns in patients 12.…”
Section: Introductionmentioning
confidence: 99%